2014
DOI: 10.3233/ch-131648
|View full text |Cite
|
Sign up to set email alerts
|

Hemorheological changes in ischemia-reperfusion: An overview on our experimental surgical data

Abstract: Thank you for your recent submission of the manuscript entitled "Hemorheological changes in ischemia-reperfusion: an overview on our experimental surgical data."It has been assigned tracking number 12-131-R.To obtain the history and current status of your manuscript, visit the address presented below and enter your last name as username and the tracking number as password.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Our results suggest that those animals which show very significant falls in microcirculatory impairment during the shock period never return to baseline values of perfusion, in contrast to those with more modest initial falls in perfused vessel density. Possible explanations for persisting microcirculatory failure after restoration of systemic blood flow include dysfunction of any or all of the individual elements that make up the microcirculation, for example, endothelial cell swelling caused by ischaemia and re-perfusion injury [ 22 ], clogging of small vessels with activated leucocytes [ 23 ] and dysfunction of transfused stored erythrocytes leading to vessel occlusion [ 24 ]. Our study was only designed to assess the initial response of the microcirculation to shock and resuscitation, and further studies are required to answer these interesting questions relating to the precise mechanisms behind persistent microcirculatory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that those animals which show very significant falls in microcirculatory impairment during the shock period never return to baseline values of perfusion, in contrast to those with more modest initial falls in perfused vessel density. Possible explanations for persisting microcirculatory failure after restoration of systemic blood flow include dysfunction of any or all of the individual elements that make up the microcirculation, for example, endothelial cell swelling caused by ischaemia and re-perfusion injury [ 22 ], clogging of small vessels with activated leucocytes [ 23 ] and dysfunction of transfused stored erythrocytes leading to vessel occlusion [ 24 ]. Our study was only designed to assess the initial response of the microcirculation to shock and resuscitation, and further studies are required to answer these interesting questions relating to the precise mechanisms behind persistent microcirculatory dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Because hemorheological parameters have been found to be associated with I/R [ 18 20 ], we also measured whole blood viscosity (WBV), erythrocyte sedimentation rate (ESR), and hematocrit (Htc). WBV at shear rates of 200 s −1 , 50 s −1 , and 10 s −1 was discovered to increase significantly from 3.52 ± 0.29 mPa·s/200 s −1 , 3.88 ± 0.35 mPa·s/50 s −1 , and 4.71 ± 0.48 mPa·s/10 s −1 in the sham operation group to 4.23 ± 0.42 mPa·s/200 s −1 , 4.75 ± 0.44 mPa·s/50 s −1 , and 5.68 ± 2.56 mPa·s/10 s −1 in the I/R group, respectively (each n = 6, P < 0.01; Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the development and changes in the morphological characteristics of schistocytes, the TMA score was developed to screen for TAMOF in critically ill patients as a rapid, simple marker [15]. With respect to erythrocytes, the hemorheological state after ischemia and reperfusion may negatively impact the deformability and aggregation behavior of RBCs through several complex process including acute phase reactions, free radical and in ammatory response, hemodynamic deteriorations, and coagulopathy [29]. Yu et al assessed the rheological properties of RBC after ischemic/reperfusion and reported that stiffer erythrocytes resulting from reduced deformability help increase vascular resistance by limiting movement to small tissue capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…Although changes in the microcirculation are known to play an important role in the severity of organ damage after CA, only few studies have investigated the characteristic changes for RBC deformability after CA and ischemic/reperfusion injury [36]. [29]. The limited number of studies prompts us to refer to the signi cant association between sepsis and DIC.…”
Section: Discussionmentioning
confidence: 99%